Exposure to Asian dust within a few days of delivery is associated with placental abruption in Japan: a case‐crossover study. (13th November 2019) - Michikawa, T; Yamazaki, S; Shimizu, A; Nitta, H; Kato, K; Nishiwaki, Y; Morokuma, S
Abstract : Objective: Asian dust is a natural phenomenon in which dust particles are transported from desert areas in China and Mongolia to East Asia. Short‐term exposure to Asian dust has been associated with cardiovascular disease through mechanisms such as systemic inflammation. Because inflammation is a potential trigger of placental abruption, exposure may also lead to abruption. We examined whether exposure to Asian dust was associated with abruption. Design: A bi‐directional, time‐stratified case‐crossover design. Setting and population: From the Japan Perinatal Registry Network database, we identified 3014 patients who delivered singleton births in hospitals in nine Japanese prefectures from 2009 to 2014 with a diagnosis of placental abruption. Methods: Asian dust levels were measured at Light Detection and Ranging monitoring stations, and these measurements were used to define the Asian dust days. As there was no information on the onset day of abruption, we assumed this day was the day before delivery (lag1). Main outcome measures: Placental abruption. Results: During the study period, the Asian dust days ranged from 15 to 71 days, depending on the prefecture. The adjusted odds ratio of placental abruption associated with exposure to Asian dust was 1.4 (95% confidence interval = 1.0, 2.0) for cumulative lags of 1–2 days. Even after adjustment for co‐pollutant exposures, this association did not change substantially. Conclusions: In this Japanese multi‐area study, exposure to Asian dust was associated with an increased risk of placental abruption. Tweetable abstract: Exposure to environmental factors such as Asian dust may be a trigger of placental abruption. Tweetable abstract: Exposure to environmental factors such as Asian dust may be a trigger of placental abruption.